2004
DOI: 10.1016/j.ijgo.2004.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Metformin therapy in women with polycystic ovary syndrome

Abstract: A 6-month course of metformin therapy may improve menstrual cyclicity and fertility in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The PCOS status was determined by a single adolescent gynecologist using Rotterdam criteria requiring the presence of at least two of the three criteria of (i) clinical or biochemical evidence evidence of hyperandrogenism; (ii) oligo- or anovulation (defined as less than nine periods per year); and (iii) PCOM [20]. During chart review, we identified girls who also met the National Institutes of Health (NIH) criteria for PCOS [21] requiring the presence of both oligoovulation and hyperandrogenism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCOS status was determined by a single adolescent gynecologist using Rotterdam criteria requiring the presence of at least two of the three criteria of (i) clinical or biochemical evidence evidence of hyperandrogenism; (ii) oligo- or anovulation (defined as less than nine periods per year); and (iii) PCOM [20]. During chart review, we identified girls who also met the National Institutes of Health (NIH) criteria for PCOS [21] requiring the presence of both oligoovulation and hyperandrogenism.…”
Section: Methodsmentioning
confidence: 99%
“…During chart review, we identified girls who also met the National Institutes of Health (NIH) criteria for PCOS [21] requiring the presence of both oligoovulation and hyperandrogenism. Determination of PCOM was based on adult criteria of the presence of 12 or more 2–9 mm follicles in each ovary or ovarian volume >10 mL as defined by Rotterdam criteria [20]. Subjects with untreated hypothyroidism, hyperprolactinemia, congenital adrenal hyperplasia, Cushing’s syndrome, pregnancy, androgen-secreting tumors, or a condition as the cause of hyperandrogenism were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Hirsutism has a low prevalence in Taiwanese Chinese women and Hsu et al(30) reported a prevalence of about 28%, whereas Takeshi et al(31), from Japan, noted a prevalence of 8%. On the other hand, Aruna et al(32) described a prevalence of 66% of hirsutism in Indian populations. Although clinical and biochemical hyperandrogenism is less in Japanese women, hypersecretion of LH is more prominent…”
mentioning
confidence: 99%
“…Metformin does not have an effect on the biochemical parameters of FSH, LH. This differs from some studies showing that metformin reduces the effect of LH and causes an elevation in serum FSH [29] [30] and agreed with studies showing that metformin has no effect on hormonal parameters [20] [31] [32]. Historically, the overall successful pregnancy rates after ovulation induction range from as low as 9% to as high as 25% [33].…”
Section: Discussionmentioning
confidence: 41%